Analysis Of Village Fund Management On Regional Development - Kalontong, Elia; Anggraeni, Aprilia; Tiawon, Harin (Universitas Negeri Semarang, 2019)
The obstacles faced by the Regional Government both the Village Government and the District Government are the lack of control over the management of funds originating from Village Fund Allocation. So, the purpose of this study is to analyze themanagement funds and the use of village funds on regional development in Katingan Kuala District, Katingan Regency. The type of research used was qualitative and quantitative research and used casual research methods with characteristics of causal relationship problems. The results of the research showed The results of statistical analysis proved that village fund had no effect on regional development in Katingan. In other words the increase or decrease in village fund would not have an impact on the ups and downs in the progress of regional development. However, the descriptive percentage result indicated that there was an influence of village fund on regional development in Katingan.